Assembled Organoruthenium(II) for Formaldehyde Decomposition and Hydrogen Production. Issue 7 (23rd December 2022) - Shen, Yangbin; Xu, Ying; Zhan, Yulu
Abstract: Formaldehyde decomposition is not only an attractive method for hydrogen production, but also a potential approach for gaseous formaldehyde removal. In this research, we prepare some assembled organoruthenium through coordination reaction between Ru( p ‐Cymene)Cl2 and bridge‐linking ligands. It is a creative approach for Ru( p ‐Cymene)Cl2 conversion into heterogeneous particles. The rigidity of bridge‐linking ligand enables assembled organoruthenium to have highly ordered crystalline structure, even show clear crystal lattice with spacing of 0.19 nm. XPS shows the N−Ru bond are formed between bridge‐linking ligand and Ru( p ‐Cymene)Cl2 . The assembled organoruthenium has high abundant active sites for formaldehyde decomposition at low temperature. The reaction rate could increase linearly with temperature and formaldehyde concentration, with a TOF of 2420 h −1 at 90 °C. It is promising for gaseous formaldehyde decomposition in wet air or nitrogen. Formaldehyde conversion is up to 95 % over Ru‐DAPM is 4, 4′‐diaminodiphenylmethane at 90 °C in air. Gaseous formaldehyde decomposition is a two‐steps process under oxygen‐free condition. Firstly, formaldehyde dissolve in water, and be converted into hydrogen and formic acid through formaldehyde‐water shift reaction. Then intermediate formic acid will further decompose into hydrogen and carbon dioxide. We also find formaldehyde decomposition is a synergetic catalysis process of oxygen and water in moist air. Oxygen is conducive to formic acid desorption and decomposition on the active sites, so assembled organoruthenium exhibit slightly higher conversion for formaldehyde decomposition in moist air. This work proposes a distinctive method for gaseous formaldehyde decomposition in the air, which is entirely different from formaldehyde photocatalysis or thermocatalysis oxidation. Abstract : A method for gaseous formaldehyde decomposition is proposed, which is totally different from formaldehyde catalytic oxidation. The assembled organoruthenium approach involves a totally different reaction path and mechanism for formaldehyde removal from air, even under oxygen‐free conditions. Formaldehyde conversion is up to 95 % over Ru‐DAPM is 4, 4′‐diaminodiphenylmethane at 90 °C in air.